Return Migration Governance in India during COVID-19 - International Organization for Migration (United Nations, 2023)
Authored by S. Irudaya Rajan, this Migration Research Series paper explores the impact of COVID-19 on the return migration of international and internal Indian migrants. The paper provides an overview of return migration dynamics in India and the various vulnerabilities of Indian migrants that were exacerbated during the pandemic. The paper examines the programmes and policies that supported the reintegration of migrants and makes suggestions for reintegration measures that go beyond the COVID-19 pandemic to consider not only economic reintegration but also the social and psychological experiences of return migrants.